Ринок банківських послуг з позицій сучасної науки і законодавства - Шірінян, Едвард Арамович; Шірінян, Лада Василівна (My University, 2023)
Навчальні програми за спеціальністю 072 «Фінанси, банківська справа, страхування та фондовий ринок» повинні регулярно оновлюватися, щоб охоплювати зміни чинного законодавства, а також відображати трансформації ринку банківських послуг, який постійно розвивається. Цей процес прямо впливає на якість освітньої підготовки студентів – майбутніх фахівців, а тому повинен бути в центрі уваги науковців та освітян. Метою статті є розкриття та удосконалення сутності поняття «ринок банківських послуг» і формулювання узагальненого поняття «ринок банківських послуг і банківських металів» з врахуванням реалій сьогодення і законодавчих змін в банківській сфері. Методологічною основою дослідження є системний підхід з використанням порівняльного аналізу, індукції, дедукції та узагальнення. Стаття умовно поділена на 3 частини: в першій – здійснено огляд законодавства щодо визначення банківських послуг; друга частина присвячена аналізу учасників ринку банківських послуг; в останній частині здійснено критичний огляд підходів інших дослідників та запропоновано нові визначення базових понять. Виявлено, що в фаховій літературі дотепер залишаються не висвітленими та не врахованими повною мірою законодавчі зміни щодо складу учасників та структури ринку банківських послуг України. Систематизовано та розширено коло учасників ринку банківських послуг України з врахуванням реалій сьогодення. Наведено перелік банківських послуг згідно з текстом Генеральної угоди з торгівлі послугами і аргументовано потребу імплементації в українське банківське законодавство. Запропоновано визначення поняття «ринок банківських послуг», яке враховує поведінку і взаємодію продавців та покупців банківських послуг, інших учасників ринку, попит і пропозицію на банківські послуги і метали, на банківські гроші, ціноутворення через процентні ставки та комісійні винагороди за здійснення банківських операцій. Curricula for the speciality 072 “Finance, banking, insurance and the stock market” must be regularly updated to cover changes in current legislation and reflect the transformations of the ever-evolving banking services market. This process directly affects the quality of educational training of students – future specialists and, therefore, should be the focus of attention of scientists and educators. The article aims to reveal and improve the essence of the concept of the “market of banking services” and formulation of the generalized concept of the “market of banking services and banking metals”, considering the realities of today and legislative changes in the banking sphere. The methodological basis of the research is a systematic approach using comparative analysis, induction, deduction and generalization. The article is conditionally divided into three parts: in the first part, a review of the legislation on the definition of banking services was carried out; the second part is devoted to the analysis of banking services market participants; in the last part, a critical review of the approaches of other researchers was carried out, and new definitions of basic concepts were proposed. It was found that legislative changes regarding the composition of participants and the structure of the banking services market of Ukraine have not been fully covered and considered in the professional literature. Systematized and expanded the range of participants in the market of banking services of Ukraine, taking into account the realities of today. According to the text of the General Agreement on Trade in Services, the list of banking services is provided, and the need for implementation into Ukrainian banking legislation was argued. The definition of the concept of “banking services market” was proposed, which takes into account the behaviour and interaction of sellers and buyers of banking services, other market participants, demand and supply for banking services and metals, bank money, pricing through interest rates and commissions for carrying out banking operations.
Keywords: кафедра фінансів; ринок банківських послуг; учасники ринку; процентні ставки; ціна послуги; банківські метали; market of banking services; market participants; interest rates; service price; banking metals